Effect of individual, household and regional socioeconomic factors and PM2.5 on anaemia: A cross-sectional study of sub-Saharan African countries. (February 2022) - Amegbor, Prince M.; Borges, Sergio S.; Pysklywec, Alex; Sabel, Clive E.
Highlights: The prevalence of anaemia amongst women (41%) was twice that of men (22%). Exposure to media is significantly associated with reduce risk of anaemia. Cumulative PM2.5 exposure is significantly associated with the likelihood of being anaemic. The relative risk of anaemia is high amongst regions in West Africa and Mozambique. Region-specific risk of anaemia was similar across sub-Saharan Africa after accounting for regional socioeconomic factors and PM2.5 . Abstract: There is limited knowledge on the effect of contextual and environmental factors on the risk of anaemia, as well as the spatial distribution of anaemia in the Sub-Saharan Africa region. In this study, we used multi-country data from the Demographic & Health survey (DHS) with 270, 011 observations and PM2.5 data from NASA, applied to the spatial risk pattern of anaemia in the SSA region. The prevalence of anaemia amongst women (41%) was almost twice that of men (22%). A Bayesian hierarchical model showed that individual household, neighbourhood and regional socioeconomic factors were significantly associated with the likelihood of being anaemic. 1 μg/m 3 increase in cumulative lifetime PM2.5 exposure accounted for 1% ( β = 0.011, CI = 0.008 – 0.015) increase in the likelihood of being anaemic. The results suggest the need for a multidimensional approach to tackle anaemia in the Sub-Saharan African region and identify high-risk areas for target intervention policies or programs.